Isomers of perfluoroalkyl substances and overweight status among Chinese by sex status: Isomers of C8 Health Project in China. (March 2019) - Tian, Yan-Peng; Zeng, Xiao-Wen; Bloom, Michael S.; Lin, Shao; Wang, Si-Quan; Yim, Steve Hung Lam; Yang, Mo; Chu, Chu; Gurram, Namratha; Hu, Li-Wen; Liu, Kang-Kang; Yang, Bo-Yi; et al.
Abstract: Previous investigations on the associations of polyfluoroalkyl substances (PFASs) with overweight/obesity are mixed. Moreover, little information has been reported about the association between isomers of PFASs with body mass index (BMI), waist circumference (WC) or overweight. To address this shortcoming in the literature, we conducted a study involving 1612 Chinese adults (1204 men and 408 women), ages 22–96 years old, from Shenyang, China, to analyze serum isomers of perfluorooctanesulfonate (PFOS), perfluorooctanoate (PFOA), and other PFASs. Height, weight and WC were measured by a standardized protocol of WHO. Results indicated that increased serum concentrations of all (both branched and linear) isomers of PFASs were associated with a higher prevalence of overweight, and these associations were more pronounced in women. The adjusted odds ratios (ORs) from logistic regression analyses among women were 1.45 (95% confidence interval [CI]: 1.06, 1.99) for linear PFOS isomers, 1.33 (95% CI: 1.00, 1.77) for branched PFOS isomers, 1.39 (95% CI: 1.06, 1.81) for 3 + 4 + 5m PFOS, 1.54 (95% CI: 1.08, 2.21) for linear PFOA isomers, and 1.62 (95% CI: 1.05, 2.51) for branched PFOA isomers, respectively. Associations with increased WC were yielded a similar pattern. Linear regression models also showed positive associations between PFASs and BMI or WC. In conclusion, this study suggests that PFASs and their isomers are positively associated with overweight or increased WC, and the associations are stronger in women. Furthermore, PFOA and its isomers displayed the most robust obesogenic associations. Graphical abstract: Unlabelled Image Highlights: Few studies explored the associations between isomeric PFASs and obesity in human. A large population-based study was conducted in China to assess theses associations. PFASs isomers were positively associated with overweight and increased WC. More associations of PFASs with overweight/obesity were found in women than in man. PFOA and its isomers exhibited the most robust obesogenic associations compared to other PFASs.